Drugs : (Ashgate, 2002)
This reference provides a classified arrangement of 10,000 drugs. Each entry includes the substance's molecular formula; its chemical, generic, and brand-name synonyms; and its manufacturer or supplier. There is a stronger emphasis on synonyms, with properties reported to a lesser degree. Melting and boiling points, optical rotation, density, UV absorption, solubility, and acute toxicity data are presented "whenever possible," but many of the entries lack such data.